Quadrature Signal Generator with Improved Dc Offset Compensation - STOJIC, D. (Advances in Electrical and Computer Engineering, 2021)
In this paper a second order generalized integrator (SOGI) based quadrature signal generator (QSG) is proposed with the improved DC offset compensation parameter tuning procedure. Namely, for the conventional DC rejection technique, which comprises an integrator (I) included in the SOGI, the modified parameter tuning procedure is proposed based on the set QSG response damping factor value. In this way, when compared to existing QSG tuning techniques based on empirical trial-and-error approach, simplified parameter tuning procedure is proposed based on proposed parametric equations, which enable improved QSG performance verified by simulation and experimental runs by a single-phase phase-locked loop PLL. In this way the increased SOGI based QSG DC offset compensation speed can be achieved, which is critical in various types of single phase PLL applications.